Decellularized extracellular matrix: A promising strategy for skin repair and regeneration - Shengjie Jiang; Yu Zhuang; Ming Cai; Xudong Wang; Kaili Lin (Engineered Regeneration, 2023)
The skin is an important organ of the human body that resists external threats but lacks sufficient self-regeneration ability when severe damage occurs. However, most of the available skin substitutes cannot achieve ideal restoration of complex structures and multiple functions of native skin tissues. Fortunately, the advent of decellularized extracellular matrix (dECM) offers a promising approach to overcome these obstacles. The dECM, derived from the natural extracellular matrix (ECM), possesses a similar structure and composition, which constructs an environment favorable for cell performance in regeneration. Moreover, dECM retains good bioactivity, low immunogenicity, and high availability, making it a suitable biomaterial for skin repair and regeneration. In this review, various decellularization methods and subsequent evaluations of dECM are introduced first, and the main sources of dECM are then presented. Furthermore, the recent progress of dECM-based biomaterials applied in skin regeneration and future perspectives are summarized.